2020
DOI: 10.5194/acp-2020-22
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the near-spherical shape the new black for smoke?

Abstract: Abstract. We examine the capability of near-spherical-shaped particles to reproduce the non-typical Particle Linear Depolarization Ratio (PLDR) values measured over Europe for stratospheric smoke originating from Canadian wildfires. The smoke layers were detected both in the troposphere and the stratosphere, though in the latter case the particles presented PLDR values of almost 18 % at 532 nm as well as a strong spectral dependence from the UV to the Near-IR. The assumption that the smoke particles have a nea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…If the smoke particles would have had an ideal spherical shape (consisting of a black carbon core and a thick organic carbon shell), the depolarization ratio would have been close to zero (Haarig et al, 2018), as was observed for the Canadian smoke at heights in the middle troposphere. Slight deviations from the ideal spherical form in combination with the monomodal, narrow smoke size distribution (accumulation mode shifted to larger particles with a mode diameter of 600 to 700 nm, absence of a coarse mode) (Dahlkötter et al, 2014;Haarig et al, 2018) lead to the observed enhanced depolarization values and the distinct wavelength dependence, as recently modeled by Gialitaki et al (2020) and also suggested by other modeling groups (e.g., Yu et al, 2019;Liu and Mishchenko, 2020). According to Yu et al (2019), smoke particles consist of an insoluble black carbon (BC) core that is surrounded by an almost spherical shell of organic material and other atmospheric substances.…”
Section: Lidar Observations Of Smoke Optical Propertiesmentioning
confidence: 63%
See 1 more Smart Citation
“…If the smoke particles would have had an ideal spherical shape (consisting of a black carbon core and a thick organic carbon shell), the depolarization ratio would have been close to zero (Haarig et al, 2018), as was observed for the Canadian smoke at heights in the middle troposphere. Slight deviations from the ideal spherical form in combination with the monomodal, narrow smoke size distribution (accumulation mode shifted to larger particles with a mode diameter of 600 to 700 nm, absence of a coarse mode) (Dahlkötter et al, 2014;Haarig et al, 2018) lead to the observed enhanced depolarization values and the distinct wavelength dependence, as recently modeled by Gialitaki et al (2020) and also suggested by other modeling groups (e.g., Yu et al, 2019;Liu and Mishchenko, 2020). According to Yu et al (2019), smoke particles consist of an insoluble black carbon (BC) core that is surrounded by an almost spherical shell of organic material and other atmospheric substances.…”
Section: Lidar Observations Of Smoke Optical Propertiesmentioning
confidence: 63%
“…Lidar ratios and depolarization ratios measured simultaneously at both 355 and 532 nm wavelengths are a prerequisite in efforts to successfully homogenize the overall Aeolus-CALIPSO data set of smoke optical properties later on. Simultaneously measured lidar ratios and depolarization ratios are also important parameters in aerosol typing efforts (see, e.g., Burton et al, 2012Burton et al, , 2015Groß et al, 2013;Nicolae et al, 2018;Papagiannopoulos et al, 2018) with lidars from ground and in space to improve optical models developed to simulate the smoke optical properties as a function of particle shape and size characteristics and composition (e.g., Kahnert, 2017;Mishchenko, 2018, 2020;Luo et al, 2019;Gialitaki et al, 2020). Thus, our Punta Arenas lidar observations in January 2020 can be regarded as an important contribution to the global library of aerosol optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. study of the optical properties of the non-spherical smoke particles has been performed (Gialitaki et al, 2019). This study suggest that the smoke particles were compact and almost spherical in shape.…”
Section: Particle Shape and Size Characteristicsmentioning
confidence: 92%
“…They hypothesize that the organic-coated particles were most likely solids because they either froze in the stratosphere or effloresced. Gialitaki et al (2019) modeled the optical properties (PLDR and lidar ratio at 355, 532, and 1064 nm) of the aged nonspherical smoke particles and compared the results with the respective multiwavelength lidar observation presented by Haarig et al (2018). These extensive simulations suggest that the smoke particles with particle effective radii of 550 nm were compact and almost spherical in shape.…”
Section: Particle Shape and Size Characteristicsmentioning
confidence: 95%